An introduction to anti-bribery management systems (BS 10500) : doing right things - Field, Alan (Compliance Series, 2015)
"When is a gift not a gift? When it's a bribe. For many, corporate hospitality oils the wheels of commerce. But where do you draw the line? Bribes, incentives and inducements are not just a matter of used banknotes stuffed in brown envelopes. Expenses, corporate settlement of personal bills, gifts and hospitality can all be used to influence business partners, clients and contractors. Can you afford unlimited fines? Under the Bribery Act 2010, a maximum of ten years' imprisonment and an unlimited fine may be imposed for offering, promising, giving, requesting, agreeing, receiving or accepting bribes. With such strict penalties, it's astonishing that so few companies have few or no measures in place to ensure that they are not liable for prosecution."--